The Railway Children - Nesbit, E. (Lahore Readings, 2017)
This adaptation of E. Nesbit's children's classic follows the fortunes of a group of Edwardian children whose father is wrongly jailed for treason. Exiled with their mother to a life of genteel poverty on the Yorkshire Moors, they are soon drawn to the railway at the bottom of the garden, and all kinds of adventures.
Keywords: Country life -- Railroad stories -- Families